The Mitogen-Activated Protein Kinase (MAPK) Pathway: Role in Immune Evasion by Trypanosomatids - Soares-Silva, Mercedes; Diniz, Flavia F.; Gomes, Gabriela N.; Bahia, Diana (Frontiers in Microbiology, 2016)
Leishmania spp. and Trypanosoma cruzi are the causative agents of leishmaniasis and Chagas disease, respectively, two neglected tropical diseases that affect about 25 million people worldwide. These parasites belong to the family Trypanosomatidae, and are both obligate intracellular parasites that manipulate host signaling pathways and the innate immune system to establish infection. Mitogen-activated protein kinases (MAPKs) are serine and threonine protein kinases that are highly conserved in eukaryotes, and are involved in signal transduction pathways that modulate physiological and pathophysiological cell responses. This mini-review highlights existing knowledge concerning the mechanisms that Leishmania spp. and T. cruzi have evolved to target the host’s MAPK signaling pathways and highjack the immune response, and, in this manner, promote parasite maintenance in the host.